THE ROLE OF TAHFIDZ TEACHERS IN DEVELOPING AL-QUR'AN MEMORIZATION AMONG STUDENTS AT PONDOK QUR'AN DAKWAH NW MONTONG MAS, LEPAK TIMUR - Muhammad Kamran Zain; L. Sukrizal Watoni (Journal of Education, Teaching, and Learning, 2024)
The objectives of this research are to determine the role of Tahfidz teachers in developing Al-Qur'an memorization among students at Pondok Qur'an Dakwah NW Montong Mas and to identify the supporting and inhibiting factors faced by Tahfidz teachers in this process. This research employs a qualitative approach. The data collection methods used are observation, interviews, and documentation. The findings regarding the role of Tahfidz teachers in developing Al-Qur'an memorization among students at Pondok Qur'an Dakwah NW Montong Mas Desa Lepak Timur include: shaping students to improve in terms of morals and behavior, being responsible for disciplining students to become compliant and able to memorize and maintain their Al-Qur'an memorization accurately, acting as a second parent to the students, providing motivation to students, guiding students in managing their time effectively. The supporting factors for Tahfidz teachers in developing Al-Qur'an memorization among students at Pondok Dakwah NW Montong Mas are the direct support from the headmaster and the enthusiasm of the students in participating in Qur'an memorization activities, as well as the graduation ceremony at the end of the semester which motivates students to be more diligent in memorizing the Al-Qur'an. The inhibiting factors include some students who are still not fluent in reading the Al-Qur'an due to the lack of cooperation between the homeroom teachers and the Tahfidz teachers